Corruption and market in contemporary China - Sun, Yan (Cornell Univ. Press, 2004)
The phenomenology of reform-era corruption : categories, distribution, and perpetrators -- Between officials and citizens : transaction types of corruption -- Between officials and the public coffer : nontransaction types of corruption -- Between the state and localities : the regional dynamics of corruption -- Between the state and officials : the decline of disincentives against corruption